Contesting Values in New Worldings - Ernst, Waltraud; Caixeta, Luzenir (My University, 2019)
Feminist epistemologies have promoted other worlds as not only thinkable and realizable but already materialized – at the fringes or margins or flip sides of dominating views: in new materialist accounts these practices of world making are called “other worldings”. To think the world, and hence truth and reality as plural and in process, as collaborative worldly endeavours and related to multiple entangled – or situated – speaking subjects, has been a crucial achievement of feminist epistemology until today. On this basis, the paper brings together ethical approaches from feminist new materialism with decolonial contestations of Enlightenment accounts on autonomous subjectivity towards a radical re-valuation of interrelating with others and enactments of the “methodology of the oppressed”. The city, in our view, is not only the place of neo-liberal divisions and high-tech competitions but also best suited for realizing encounter zones and creating space for transversal queer-feminist movements. maiz – Autonomous Centre by and for Migrant Women* in the city of Linz in Austria serves as an example for such a realization of theoretical and practical worlding, as we aim to show in this paper, especially with the foundation of the “University of Ignoramuses” and migrazine.at. We argue that not only this encounter zone seems promising but also its realization in the social, material and virtual space were the pleasure of networking and lived relations of solidarity, learning, un-learning and transformation can be discovered and trained with experts in the field. On this way, the paper brings together an onto-ethico-epistemological approach with an activist approach for transformation of reality.
Keywords: Epistemologie; Queer Theory; Feminismus; Aktivismus; 300 Sozialwissenschaften; transversal queer-feminist movement; onto-ethico-epistemology; counter-hegemonic knowledge; methodology of the oppressed; decolonial feminism; dissident feminisms; transformation of reality; European values; activism; ontological relationality